2013
DOI: 10.1183/09031936.00146012
|View full text |Cite
|
Sign up to set email alerts
|

Lung function indices for predicting mortality in COPD

Abstract: Chronic obstructive pulmonary disease (COPD) is characterised by high morbidity and mortality. It remains unknown which aspect of lung function carries the most prognostic information and if simple spirometry is sufficient.Survival was assessed in COPD outpatients whose data had been added prospectively to a clinical audit database from the point of first full lung function testing including spirometry, lung volumes, gas transfer and arterial blood gases. Variables univariately associated with survival were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
75
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 57 publications
4
75
1
3
Order By: Relevance
“…8,13,16,21 Improved gas transfer is important as this may be the lung function variable most strongly associated with survival in patients with COPD. 22 In our previous study of upper lobe ELVR (n = 21), we also showed that gas transfer function in severe COPD patients who had ELVR, improved significantly at 12 months. 13 In this study, although there was a trend towards improved KCO this did not reach statistical significance due to both small numbers and incomplete follow-up at this time.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…8,13,16,21 Improved gas transfer is important as this may be the lung function variable most strongly associated with survival in patients with COPD. 22 In our previous study of upper lobe ELVR (n = 21), we also showed that gas transfer function in severe COPD patients who had ELVR, improved significantly at 12 months. 13 In this study, although there was a trend towards improved KCO this did not reach statistical significance due to both small numbers and incomplete follow-up at this time.…”
Section: Discussionsupporting
confidence: 52%
“…There is some evidence that ELVR may reduce dynamic hyperinflation and improve exercise capacity in association with improvements in inspiratory capacity and gas transfer (KCO) . Improved gas transfer is important as this may be the lung function variable most strongly associated with survival in patients with COPD . In our previous study of upper lobe ELVR ( n = 21), we also showed that gas transfer function in severe COPD patients who had ELVR, improved significantly at 12 months .…”
Section: Discussioncontrasting
confidence: 51%
“…Th is, together with the recent reports on the predictive value of impaired DLco for COPD mortality and exacerbations (18,45), implies that DLco should be used to a greater extent in the routine evaluation of patients with COPD. Th is could also give relevant clinical information in order to initiate a more integrated approach to the patient's cardiopulmonary status and possibly identify treatable underlying conditions, such as coexistent heart failure (46).…”
Section: Discussionmentioning
confidence: 92%
“…A number of publications suggest that DLco is closely linked to impaired exercise capacity, elevated infl ammatory biomarkers and arterial oxygen desaturation in patients with COPD (15)(16)(17). Furthermore, DLco has been found to be an independent predictor of mortality in COPD patients (18). However the impact of DLco on walking distance and walking distance changes over time has been limitedly investigated in COPD patients.…”
Section: Introductionmentioning
confidence: 98%
“…Among the complications most feared by patients with chronic obstructive pulmonary disease (COPD) is the need to use domiciliary oxygen (1,2), yet there are clear data to show that when Pa O 2 is less than 7.3 kPa, supplemental oxygen extends life (3)(4)(5).…”
mentioning
confidence: 99%